The protective effect of the Rho-kinase inhibitor hydroxyfasudil on propofol-induced hippocampal neuron apoptosis in neonatal rats - Li, Xuze (Int J Clin Exp Pathol, 2018)
Propofol is widely applied for anesthesia induction in pediatric patients. However, accumulating evidence has proved that propofol is neurotoxic to the immature or developing brain. In the present study, we found that hydroxyfasudil, a specific inhibitor of Rho kinase, alleviated the apoptotic neurodegeneration induced by propofol in the developing rat brain. A spatial probe test and Morris water maze test revealed that hydroxyfasudil showed a potential improvement of the tendency towards cognitive impairments induced by propofol. Mechanistically, hydroxyfasudil markedly ameliorated the activation of RhoA and the expression of Rock1, Rock2, Bak, Bax, and Bad induced by propofol and rescued the expression of Bcl2 suppressed by propofol. Our findings suggest that hydroxyfasudil may serve as an effective agent to reduce the propofol-induced neurotoxic effects in pediatric medical procedures.